2010
DOI: 10.1074/jbc.m110.141176
|View full text |Cite
|
Sign up to set email alerts
|

A Minimal Cysteine Motif Required to Activate the SKOR K+ Channel of Arabidopsis by the Reactive Oxygen Species H2O2*

Abstract: Reactive oxygen species (ROS) are essential for development and stress signaling in plants. They Reactive oxygen species (ROS) 3 are major signals in virtually every aspect of eukaryotic cell biology (1, 2). In animals, they are important regulators of cell division and muscle contraction among others (3), and in plants they are essential for development (4) and stress signaling, including drought (5, 6) and defense against pathogens (7). Within proteins, ROS target a small subset of amino acids, notably cys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
80
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(81 citation statements)
references
References 46 publications
1
80
0
Order By: Relevance
“…Allen et al, 2000;Foreman et al, 2003;Demidchik et al, 2007) and molecular levels (e.g. the Ca 2+ -permeable Stelar K + Outward Rectifier or Annexin1; Garcia-Mata et al, 2010;Richards et al, 2014; Fig. 1), although to date the relevant channels related to systemic signaling have not been identified.…”
Section: Ros Rbohs and The Calcium Wavementioning
confidence: 99%
“…Allen et al, 2000;Foreman et al, 2003;Demidchik et al, 2007) and molecular levels (e.g. the Ca 2+ -permeable Stelar K + Outward Rectifier or Annexin1; Garcia-Mata et al, 2010;Richards et al, 2014; Fig. 1), although to date the relevant channels related to systemic signaling have not been identified.…”
Section: Ros Rbohs and The Calcium Wavementioning
confidence: 99%
“…However, although the details of the signaling pathways are being elucidated (Wrzaczek et al, 2015), information on the identity of the initial targets that are affected by ROS is still relatively scarce. These targets, which are presumably subject to ROS-induced oxidation, may include lipids or sensitive Cys residues on proteins such as ion channels (Garcia-Mata et al, 2010).…”
Section: How Are Ros Signals Perceived and Transmitted To The Nucleus?mentioning
confidence: 99%
“…The molecular identities of ROS-regulated Ca 2+ -permeable channels in plants have remained obscure, despite their manifest significance in growth, adaptation, and defense (Dodd et al, 2010). The Ca 2+ -permeable Stelar K + Outward K + Rectifier PM channel (Gaymard et al, 1998) has been shown to be activated by hydrogen peroxide in a heterologous expression system (Garcia-Mata et al, 2010), but the effects of ROS on its Ca 2+ permeation, ability to affect [Ca 2+ ] cyt , and where it lies in relation to NADPH oxidase activity are unknown. Maize ANN33/ANN35 have previously been shown to form a hyperpolarization-activated macroscopic Ca 2+ conductance in PLBs containing malondialdehyde (to mimic peroxidized PM; Laohavisit et al, 2010).…”
mentioning
confidence: 99%